Disease Facts: otitis externa. Issue 10 (December 2013) - Craig, Mark
<x xml:space="preserve">Abstract</x> This article discusses otitis externa, inflammation of the external ear canal, the classification of which has been modified to include a combination of causes and factors. Primary and secondary causes, predisposing and perpetuating factors, clinical features, diagnosis, treatment and prognosis are considered.